Radical Evil in the Lockean State: The Neglect of the Political Emotions - Nussbaum, Martha (Journal of moral philosophy, 2006)
Abstract All modern liberal democracies have strong reasons to support an idea of toleration, understood as involving respect, not only grudging acceptance, and to extend it to all religious and secular doctrines, limiting only conduct that violates the rights of other citizens. There is no modern democracy, however, in which toleration of this sort is a stable achievement. Why is toleration, attractive in principle, so difficult to achieve? The normative case for toleration was well articulated by John Locke in his influential A Letter Concerning Toleration , although his attractive proposal thus rests on a fragile foundation. Kant did much more, combining a Lockean account of the state with a profound diagnosis of ‘radical evil’, the tendencies in all human beings to militate against stable toleration and respect. But Kant proposed no mechanism through which the state might mitigate the harmful influence of ‘radical evil’, thus rendering toleration stable. One solution to this problem was proposed by Rousseau, but it has deep problems. How, then, can a respectful pluralistic society shore up the fragile human basis of toleration, especially in a world in which we need to cultivate toleration not only within each state, but also among peoples and states, in this interlocking world?